Genital Self-Image and Considerations of Elective Genital Surgery. Issue 2 (17th February 2017) - Smith, Nicole K.; Butler, Scott; Wagner, Brandon; Collazo, Erika; Caltabiano, Lucia; Herbenick, Debby
Abstract : The present study explores how genital self-image may be related to considerations of surgically altering one's genitals and documents the wanted genital changes among young adults. Evidence of a nontrivial proportion of respondents (98 of 1, 110) had seriously considered elective genital surgery. Regression models indicate that, for both men and women, identifying as heterosexual and reporting lower composite genital self-image scores results in higher odds of considering genital surgery. Additionally for men, feeling unsatisfied with penis size increased the odds. Clinical and educational efforts to normalize and celebrate genital variation may influence considerations for genital modification in young adults.